Assessment of Drug Utilization Pattern in Chronic Kidney Disease Patients in A Tertiary Care Hospital Based on Who Core Drug Use Indicators - Sharad Chand; C. S Shastry (Journal of Global Pharma Technology, 2019)
Introduction: Chronic kidney disease (CKD) is defined as any decrease in the glomerular filtration rate (GFR) with an abnormality in the kidney structure or its function. CKD patients are presented with multiple co-morbidities and compromised pharmacokinetics resulting in compromised quality of life and considerable economic burden. Aim: To study the drug utilization pattern in Chronic Kidney Disease (CKD) patients by using the World Health Organization (WHO) core drug use indicators. Materials and Method: A prospective observational drug utilization study was carried out in out-patients of Department of Nephrology of Justice K S Hegde Charitable Hospital, Mangaluru, for period of 8 months. CKD patients with an age of 18 years and above were included with consent. Data was collected using data collection forms, patients case notes, prescriptions sheet and personal interviews. Result: A total of 256 patients were recruited. Of which, 192 (75%) patients were males and 64(25%) were females with a mean age of 54.5 years. Average consultation time was 6.5 minutes. A total of 1374 drugs were prescribed to these patients with an average of 5.3 drugs per prescription. The most common prescribed class of drugs were for the cardiovascular system (42.6%) followed by the hematopoietic system (16.7%). Further, 65% of the drugs were prescribed from the National list of essential medicines (NLEM) whereas 8.7% of drugs were prescribed by generic name. Conclusion: Utilizing the WHO’s core drug use indicators in this special patient population will strengthen the current hospital drug use policies and improve the drug usage pattern, saving the precious life years and monetary resources.